Comparison of lightning return stroke channel-base current models with measured lightning current - Chin-Leong Wooi; Zulkurnain Abul-Malek; Mohamad Nur Khairul Hafizi Rohani; Ahmad Muhyiddin Bin Yusof; Syahrun Nizam Md Arshad; Ali I Elgayar (Bulletin of Electrical Engineering and Informatics, 2019)
Electromagnetic pulse radiation produced around the lightning stroke channel has caused the disturbance to the microelectronic industry, especially to disturbance of high frequency to electronic systems. Lightning channel-base current function (CBC) characteristics and parameters determine lightning electromagnetic field (LEMF) results obtained on the basis of the used models. This paper evaluated and compared the measured lightning current and six lightning current-based channels models namely Bruce and Golde, Heidler, Diendorfer and Uman, Nucci, Pierce and Cianos and new current-based current (NCBC) models. In terms of the waveshape, among all the six lightning channel-based current models discussed, the models developed by Javor, Nucci and Diendorfer and Uman have showed a good agreement compared to the measured lightning current. In terms of 10-90% risetime and full width half maximum time (FWHM) comparison, NCBC and Nucci models have showed compatible comparison. However, Nucci model is not easily adjustable to different desired pulse-current waveshapes. On the other hand, NCBC model can be simplified, the values of lightning peak current and risetime can be chosen arbitrarily and independently from other parameters, and there is no need for the peak-correction factor, so that reduces the number of parameters. Therefore, the NCBC model was suggested to be used in the future in order to simulate much accurate return stroke model. This knowledge will contribute to the development of a new accurate and efficient return stroke model.